x2 - y2 + xy = 1 => y2 = x2 + xy - 1
Thay vào 3x + y = y2 + 3 ta được:
3x + y = x2 + xy - 1 + 3
=> x2 - x + xy - y - 2x + 2 = 0
=> (x - 1)(x + y - 2) = 0
\(\Rightarrow\left[\begin{matrix}x-1=0\\x+y-2=0\end{matrix}\right.\)
+) x - 1 = 0 => x = 1, thay vào x2 - y2 + xy = 1 ta được:
12 - y2 + 1.y = 1 => y - y2 = 0
=> y(1 - y) = 0
\(\Rightarrow\left[\begin{matrix}y=0\\y=1\end{matrix}\right.\)
+) x + y - 2 = 0 => x = 2 - y
Thay vào 3x + y = y2 + 3 ta được:
3(2 - y) + y - y2 - 3 = 0
=> 3 - y2 - 2y = 0
=> y2 + 2y - 3 = 0
=> (y - 1)(y + 3) = 0
\(\Rightarrow\left[\begin{matrix}y=1\\y=-3\end{matrix}\right.\)
Giá trị tương ứng của x là: 1; 5
Vậy ...